Edukasi Dan Demo Puding Daun Kelor Bagi Kader Kesehatan Untuk Mencegah Stunting Di Wilayah Puskesmas Jatimulya - Karo, Marni Br; Sirait, Lenny Irmawaty; Manulang, Riyen Sari; Junita, Friska; Telaumbanua, Linda K; Tamba, Ezra; Yuanita, Irma; Rachmawati, Umi; Surwatini, Nunung; Kurniawati, Shinta; Handayani, Fauziah; Rakhmawati, Yuni; Amanah, Siti; Oktavia, Siska; Purba, Roma Deliana; Nurmaliha, Tati; Lestari, Alviani Cahya; Nurmaulida, Silvina; Maulani, Oktari; Khadmiati, Khadmiati; Yuliana, Hanita Indra; Pratiwi, Alvinda (Universitas Bakti Tunas Husada, 2026)
Stunting is a serious concern in Indonesia due to inadequate nutrition in children, which impacts physical growth and brain development. The government is actively working to reduce stunting rates throughout Indonesia. One effective way to address this is by utilizing moringa leaves as a nutritional supplement, given their rich nutritional content and widespread availability. This community service project aims to improve the knowledge and skills of mothers and health workers in stunting prevention through education and demonstrations of making moringa leaf pudding. Moringa leaves were chosen for their high nutritional content and easy availability as a food additive. The activity took place at the Jatimulya Community Health Center (Puskesmas) and involved 20 participants, consisting of mothers and health workers with toddlers and preschoolers. The methods used included education on the benefits and nutritional content of moringa leaves as an alternative to prevent stunting, as well as a demonstration of how to make moringa leaf pudding. Before and after the education, participants completed questionnaires to assess their understanding of the material. The results showed an increase in participants' knowledge regarding the use of moringa leaves in preventing stunting. Participants were also enthusiastic and actively participated in the activities. This approach is expected to strengthen stunting prevention efforts in the region and improve children's nutritional intake sustainably.